Press Handling Frameworks of Baghdad Conference for Dialogue and Partnership – An Analytical Study on Russia Today Website - Mohammed Samir Ali, Assistant Lecturer: (lark, 2022)
The media often resorts to framing important topics, especially the political ones, because of their importance to their goal in conveying these topics. The Baghdad Conference for Dialogue and Partnership is one of the important political issues that have occurred on the international political scene in general and the Arab and Iraqi. So it was necessary to study the frameworks of journalistic treatment used by Russia Today in Arabic for the Baghdad Conference on Dialogue and Partnership that was held in Baghdad in August 2021, especially since Russia is one of the most important countries that has its political and military weight in the region, as well as its non-attendance and invitation to the conference, which made its choice more appropriate and correct, being a neutral country that is not participating in the conference. This research seeks to reveal the topics that the study site focused on in dealing with the subject of Baghdad Conference to show the most important media frameworks used in the study site in its treatment of the topic of Baghdad Conference, as well as to identify the types of journalistic treatments that the study site used in dealing with the topic of Baghdad Conference, as this research is a descriptive one and the researcher relied on the analytical survey method, in which the researcher conducted an analytical study using content analysis for the period from 1/8/2021 to 15/9/2021 based on the comprehensive inventory method of the conference topics that reached, during the study period, (113) subjects. The researcher reached important results, the most prominent of which is that the political framework of the strategy came first among the journalistic frameworks used on the Russia Today website in its treatment of the subject of Baghdad Conference, as it came at a rate of (50.4%), in addition to that, the treatment of the study site for Baghdad Conference was. It came in the first place with a rate of (38.9%).